Dos nuevas especies de bagres del género Trichomycterus (Siluriformes: Trichomycteridae) de la Gran Sabana, Escudo de las Guayanas, Venezuela - Lasso, Carlos A (2002)
Trichomycterus celsae n. sp. and Trichomycterus lewi n. sp. are described from the river Kukenán a tributary of the river Caroní, Orinoco basin, Guyana Shield, Venezuela. The new species are diagnosed within the Guyana Shield Trichomycterus species by a distinctive color pattern. Trichomycterus celsae has a uniform light brown color on dorsum and sides of the body; the ventral surface is yellowish or creamy. Trichomycterus lewi has an irregular pattern of black spots of different sizes on dorsum and sides of the body, the larger spots are located at the posterior part of the body, and, the ventral surface is whitish. The osteology of the new species showed that they belong to the genus Trichomycterus. Osteological features support the external diagnosis of both species, some of them are: in T. celsae, the skull has the fontanels well separated, T. lewi has the fontanels closer and joined by a narrow canal. In T. celsae, the dorsal border of the hyomandibula has a conspicuous notch. In T. lewi, the metapterygoid has a projection on the posteroventral angle. Neural spine of the first preural centra is more elongated in T. lewi.